New type of cave in the Tien Phuoc District, Quang Nam Province, Viet Nam - Nguyen, Giang Thi Truong; Xuan, Nam Nguyen; T, Hieu P.; Pham, Minh (Indonesian Journal of Geography, 2025)
Cave systems in Vietnam typically develop in limestone terrains, which cover about 20% of the national territory and are concentrated mainly in the north. In contrast, Tien Phuoc District (Quang Nam Province) is located in central Vietnam, featuring a hilly topography composed primarily of metamorphic rocks, with no previously recorded limestone terrain. The recent discovery of "Bat Cave," a notable scenic site in this region, has revealed a new type of cave development. Through geological, geomorphological surveys, and petrology analysis, the study identifies that Bat Cave formed within lime-bearing metamorphic rocks. Surface features, such as karren landforms—typically associated with karst terrain—indicate significant chemical weathering due to rainwater. The cave walls and floor also show signs of fluvial dissolution. Additionally, tectonic activity, including faulting and uplift, appears to have influenced the cave's formation, interacting with exogenous processes to shape the current landscape. These findings enhance the understanding of cave formation in non-limestone terrains and provide scientific support for recognizing geological heritage in Central Vietnam. This contributes to the foundation for establishing a future geopark in the region.